2013
DOI: 10.1093/icvts/ivs554
|View full text |Cite
|
Sign up to set email alerts
|

Wound complications after median sternotomy: a single-centre study

Abstract: Wound complications following median sternotomy remain a challenge to cardiac surgery. Redo and emergency operations are the most important risk factors in this contemporary series. More efforts seem mandatory to decrease this arduous morbidity and the costs of prolonged treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 21 publications
2
59
2
4
Order By: Relevance
“…CABG, coronary artery bypass graft; HTx, heart transplantation; NPS, no prior sternotomy; VAD, ventricular assist device; SE, standard error. difference in the frequency of infection or sternum infection between both groups [3,5,7,12], whereas others found an higher incidence of infection, drug-treated infection, or death caused by infection in PS group patients [6,8,9,13]. Our analysis of the UNOS database showed an higher incidence of drug-treated infections in PS group patients [10].…”
Section: Figmentioning
confidence: 55%
“…CABG, coronary artery bypass graft; HTx, heart transplantation; NPS, no prior sternotomy; VAD, ventricular assist device; SE, standard error. difference in the frequency of infection or sternum infection between both groups [3,5,7,12], whereas others found an higher incidence of infection, drug-treated infection, or death caused by infection in PS group patients [6,8,9,13]. Our analysis of the UNOS database showed an higher incidence of drug-treated infections in PS group patients [10].…”
Section: Figmentioning
confidence: 55%
“…A high BMI has been associated with postoperative atrial fibrillation [25], superficial infection [26], deep sternal infection [27], and readmission to the intensive care unit [28] after cardiac surgery. The BMI in both groups in our study was below the risk levels reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Antsvorio turintys pacientai turi padidėjusią pooperacinių komplikacijų atsiradimo riziką. Atliekant vidurinę sternotomiją, antsvoris yra žaizdos infekcijos, hospitalinės pneumonijos, ilgesnės aortos užspaudimo trukmės ir ilgesnės dirbtinės kraujo apytakos rizikos veiksnys [2,3,4].…”
Section: Aktualumasunclassified